One-pot microwave-assisted combustion synthesis of Ni-Al2O3 nanocatalysts for hydrogen production via dry reforming of methane. (1st March 2021) - Medeiros, Rodolfo L.B.A.; Figueredo, Gilvan P.; Macedo, Heloísa P.; A.S. Oliveira, Ângelo; Rabelo-Neto, Raimundo C.; Melo, Dulce M.A.; Braga, Renata M.; Melo, Marcus A.F.
Graphical abstract: Abstract: Ni-based catalysts supported on Al2 O3 were obtained via a simple, low cost and fast one-pot microwave-assisted combustion synthesis. The effect of fuel content (urea) was investigate. It was observed that the fuel ratio greatly influences the catalysts properties and performance. The results showed that the catalyst synthesized with low fuel content (Ni-LU) presented high specific surface area (265 m 2 /g), high degree of reduction and smaller nanometric Ni particles (~15 nm). In addition, the catalytic tests carried out at 700 °C for 20 h (GHSV = 72 Lh −1 g −1 ) revealed high activity with low coke deposition. Further investigations were conducted on Ni-LU catalyst in order to better understand its catalytic properties. In-situ X-ray diffraction analysis (using synchrotron radiation) was used to evaluate the Ni particle size during the DRM, and indicated the sintering of Ni particles during the first hour of catalytic reaction. Furthermore, small amount of carbon nanotubes (CNT) with Ni particles encapsulated were observed by TEM analysis.